Study of Ethylene-Removing Materials Based on Eco-Friendly Composites with Nano-Tio2 - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Valenzuela-Bascunan, X; Galotto-Lopez, M; Torres-Mediano, A (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Ethylene is a phytohormone that is responsible of fruit and vegetable ripening. TiO2 has been studied as a possible solution to slowing down unwanted ripening processes, due to its photocatalytic capacity which enables it to remove ethylene. Thus, the objective of this study was to develop nanocomposites based on two types of eco-friendly materials: Mater-Bi® (MB) and poly(lactic acid) (PLA) combined with nano-TiO2 for ethylene removal and to determine their ethylene-removal capacity. First, a physical–chemical characterization of nano-TiO2 of different particle sizes (15, 21, 40 and 100 nm) was done through structural and morphological analysis (DRX, FTIR and TEM). Then, its photocatalytic activity and the ethylene-removal capacity were determined, evaluating the effects of time and the type of light irradiation. With respect to the analysis of TiO2 nanoparticles, the whole samples had an anatase structure. According to the photocatalytic activity, nanoparticles of 21 nm showed the highest activity against ethylene (~73%). The results also showed significant differences in ethylene-removal activity when comparing particle size and type and radiation time. Thus, 21 nm nano-TiO2 was used to produce nanocomposites through the melt-extrusion process to simulate industrial processing conditions. With respect to the nanocomposites’ ethylene-removing properties, there were significant differences between TiO2 concentrations, with samples with 5% of active showed the highest activity (~57%). The results obtained are promising and new studies are needed to focus on changes in material format and the evaluation in ethylene-sensitive fruits. © 2023 by the authors.